Kajian Perkembangan Aktivitas Sosial dan Rekreasi di Jalur Pedestrian (Studi Kasus : Jalur Pedestrian Jalan Pahlawan) - Pratitis, Anggar (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Pedestrian path, besides having the main function as sidewalk, it also has other function  for other activities such as recreational and social activities (Rapoport, 1977). One of the pedestrian path in Semarang which develops for the activity  is  pedestrian path on Pahlawan street. On that pedestrian path, the function as sidewalk doesn't develop well. On the contrary ,that pedestrian path is used  for recreational activities and social activities (Pattisinai, 2011). Interestingly, pedestrian path on Pahlawan street is also the location for some  formal offices and there is no facilities to support social and recreational activities. Based on this problem, this study aims to examine the phenomenon of social and recreational activities on the pedestrian path by looking at the relation between activity and space. The analytical method which is used is a combination of quantitative and qualitative methods were performed by mixing the two methods that are unbalanced, called Concurrent Embedded (Mixed unbalanced) (Sugiyono, 2013). Results from this study is that there is a relationship of mutual influence and are influenced between space and activity at pedestrian path on Pahlawan street. Social and recreational activities that take place at the pedestrian path on Pahlawan street make a different atmosphere and attractive place and increase the quality of existing space.